A legal study on the effectiveness of Sale of Drugs Act 1952 and its regulations in controlling the sale of cosmetic products in Malaysia / Norhidayah Mohamad - Mohamad, Norhidayah (2018)
In Malaysia, the control of the sale of cosmetic products is governed by Sale of Drugs Act 1952 and Control of Drugs and Cosmetics Regulations 1984. According to this Act and its regulations, cosmetic products in Malaysia need to be notified before it can be placed in the local market without any requirement for the quality test during the notification process. This provides a huge potential risk to the consumer due to they might be exposed to the cosmetic products containing harmful ingredients. Therefore, the objectives of the study are to examine the adequacy of the current provisions in the Sale of Drugs Act 1952 and its regulations in controlling the sale of cosmetic products in Malaysia; to identify and analyze other country laws such as China in controlling the sale of cosmetic products; and to propose recommendations to improve the current legislation in order to minimize the problems. The methodology used in this study is a doctrinal study which is library-based. All the relevant information collected based on the Sale of Drugs Act 1952 and its regulations; and also from reports, journals, newspaper, articles and websites. The other method used is empirical research whereby interview schedule and interview questions were used as research instruments. All data were transcribed and analyzed accordingly. This study found that there is an inadequacy in the current legislation. Notification process only involved submission of certain documents and does not require any test done by the authority to ensure the safety and quality of the cosmetic products. Although post-marketing surveillance carried out by the National Pharmaceutical Regulatory Agency after the cosmetic products have been marketed, it is not compulsory for all cosmetic products and priority given to whitening cosmetic products. In addition, there is no compulsory to attach the notification number to the label of cosmetic products. As compared to China, all imported cosmetic products need to undergo quality and safety test performed by an institution or organization appointed by their authority as one of the requirements for registration before it can be sold in the local market. The cosmetic product owner also needs to attach registration number on the product label, so that the consumers can distinguish whether the cosmetic products are registered or not. Therefore, this mechanism can guaranty the quality and the safety of the cosmetic products to end user and the risk of harmful cosmetic products can be reduced. Hence, there is a need to improve the law to curb the problems. The study result may benefit the Pharmaceutical Services Division, Ministry of Health as the policy makers and also may help the consumer to use safe cosmetic products.